Pengaruh Literasi Keuangan dan Modal Usaha Terhadap Keunggulan Kompetitif UMKM Di Wilayah Cikarang - Aisatu Rahma; Bunga Puja Ananda; Iis Fauziah; Sekar Asri Pebri Wulandari; Retno Purwani Setyaningrum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Financial literacy is considered an individual's ability to understand and manage finances effectively, while venture capital reflects the financial resources used to run and grow a business. Competitive advantage is measured based on the ability of MSMEs to compete through innovation, operational efficiency and product differentiation. Therefore, this study aims to analyze the effect of financial literacy and business capital on the competitive advantage of micro, small and medium enterprises (MSMEs). The research method used is quantitative with a survey approach to a number of MSME actors. The sample in this study is micro, small and medium enterprises (MSMEs) in the Cikarang Region with a total of 65 respondents. The results showed that financial literacy has a positive and significant effect on competitive advantage. In addition, business capital also has a positive influence on competitive advantage.